A Novel Arthroscopic Inside-Out Repair Technique for PASTA Lesions - Caldwell, Lindsey S. (Arthrosc Tech, 2014)
There is no current consensus in the literature on the optimal technique for surgical treatment of partial articular-sided supraspinatus tendon avulsion (PASTA) lesions, although most techniques described to date require takedown of the partially torn tendon or passage of an anchor through the already damaged tendon. We describe a novel inside-out repair technique for partial articular surface supraspinatus tears that does not require further disruption of the partially torn tendon by passage of an anchor.